Risk Management Practices in the Purchasing System of an Automotive Company - Anabela Tereso; Cláudia Santos; João Faria (Systems)
This paper presents the results of a case study conducted in the purchasing department of Bosch Car Multimedia Portugal, aiming to analyze and improve risk management practices within its project environment. Projects in this department are characterized by high complexity and uncertainty, making effective risk management essential. The study adopts a multi-method qualitative approach, integrating document analysis, direct observation, semi-structured interviews, and questionnaires. A comprehensive literature review established the theoretical foundation and guided the identification of best practices in project risk management. The field research revealed significant gaps in the structuring, standardization, and cultural integration of risk management processes. A comparative analysis between theoretical models and current practices led to the development of a tailored risk management framework, including a practical good-practices manual and a workshop format designed to promote internal engagement and capacity-building. This work contributes both theoretically—by validating literature-based models in an industrial setting—and practically, by offering replicable tools for similar departments in the automotive sector. The findings highlight the necessity of fostering a proactive risk culture to ensure the sustained implementation and effectiveness of the proposed measures.